Shade stress on maize seedlings biomass production and photosynthetic traits - Yuan,Liuzheng (2022)
ABSTRACT: The responses of two maize (Zea mays L.) cultivars, ‘LY336’ (shade tolerant) and ‘LC803’ (shade sensitive), to shade stress in a pot experiment conducted in the 2015 and 2016 growing seasons were investigated. The impact of 50% shade stress treatment on shoot biomass, photosynthetic parameters, chlorophyll fluorescence, and malondialdehyde (MDA) content was evaluated. The shoot biomass of the two maize hybrids was decreased significantly by shade stress treatment, for shade stress 7 d, the LC803 and LY336 were reduced by 56.7% and 44.4% compared with natural light. Chlorophyll fluorescence parameters of LY336 were not significantly affected by shade stress, whereas those of LC803 were significantly affected, the Fo increased under shade stress; however Fm, FV/FM and ΦPSII were decreased under shade stress. Among photosynthetic parameters measured, net photosynthetic rate (Pn), stomatal conductance (Gs), and transpiration rate were significantly decreased compared with natural light, LY336 and LC803 reduction by 28.0%, 22.2%, 57.7% and 35.5%, 18.9%, 62.4%; however, intercellular CO2 concentration (Ci) was significantly increased, for the two cultivars. Under shade stress for different durations (1, 3, 5, 7 d), Pn, Gs, Ci, and MDA content differed significantly between the two cultivars. Results indicated that different maize genotypes showed different responses to shading. Shade-tolerant genotypes are only weakly affected by shade stress.